THE INFLUENCE OF ACUPUNCTURE THERAPY ON IRREGULAR MENSTRUATION IN ADOLESCENTS - Masruroh, Masruroh; Siti Muniroh (International Journal of Social Science, 2021)
Women's reproductive health starts from puberty which is marked by menstruation. Menstruation is a cyclical, regular shedding of the lining of the uterus, in response to the interaction of hormones produced by the hypothalamus, pituitary, and ovaries. Irregular menstruation is a condition of women who experience menstrual cycle disturbances. Menstrual cycles are usually the most irregular around menarche and menopause (Reed and Carr 2015). Several conditions can cause menstrual disorders including psychological stress, disease, hormonal disorders and nutritional status. Teenagers who enter a new environment with burdens and adaptations can cause menstrual disorders, including irregular menstruation. The impact of irregular menstruation can cause anemia, weakness and impaired concentration. overcome the problem of irregular menstruation, nursing can use complementary therapy as an alternative therapy to overcome the client's problem with the support ofevidence based practice and nursing theory according to client needs, through acupuncture(Widyatuti 2008).Complementary therapy in nursing is increasingly in demand as an alternative in helping to solve client problems on the basis of utilizing energy balance in the body through stabbing certain points in the body (Snyder and Lindquist 2002). The purpose of this study was to analyze the effect of acupuncture complementary therapy on irregular menstruation in adolescents in Pondok Darul Ulum Islamic Boarding School, Jombang. This type of research is analytic with a research designquasy experimentalapproachpre test post tes control group desain. The study population was adolescents at Darul Ulum Jombang Islamic Boarding School who met the inclusion criteria of 550 people. The sample in this study were 138 people with techniquessimple random sampling. The intervention was given to 35 people and a control group of 35 people. The results of the analysis using the T test showed that the intervention group in adolescents with irregular menstruation averaged 73.2500, while in the control group it was 61.280. while the Sig.(2-tailed) value is 0.009. This shows that there is a difference between the intervention group and the control group. There is a significant effect of acupuncture on irregular menstruation in adolescents. Nurses need to consider acupuncture as a complement in overcoming the problem of irregular menstruation.